Climate services for farmers - CGIAR Research Program on Climate Change, Agriculture and Food Security (2011)
Climate information services are a concrete and powerful tool that live up to the promise of adaptation—helping farmers adjust to the impacts of climate variability and change—to both protect against drought and take advantage of good conditions. Across Africa and Asia, the CGIAR Research Program on Climate Change, Agriculture and Food Security (CCAFS) is learning from, evaluating and implementing initiatives that bring climate services to farmers.